What Expertise Can Tell About Mathematical Learning and Cognition. Issue 4 (17th October 2018) - Sella, Francesco; Cohen Kadosh, Roi
ABSTRACT: The investigation of mathematical expertise can shape numerical and mathematical cognition theories by providing insights about the modifications that the neurocognitive system undergoes when mastering mathematical knowledge. In particular, both qualitative and quantitative methods should be combined within a developmental perspective to identify those promoting factors that lead some individuals to focus their interests on mathematics and possibly become experts in the field. The behavioral and neural differences in math experts constitute valuable information to study the limits of the mastering of mathematical knowledge, which ultimately represents a powerful form of formal human reasoning.